COMMUNITY IN DIVERSITY. A PLEA OF A SUBSTANTIAL MULTILINGUALISM IN A COMMON EUROPE - Lönz, Michael (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
http://dx.doi.org/10.7220/2335-2027.3.4 To understand Europe means to understand diversity, diversity in culture, political practice and also in language. But in the multilingual Europe multilingualism is threatened, e.g., by a predominant English. Therefore, the EU Commission is promoting “linguistic diversity”. The paper discusses what could be meant with this term. First, it is necessary to say that monolingualism accompanied only the rising of the national state in the 19th and 20th century. Then the position of a lingua franca was questioned in the modern world, especially, in modern Europe, to defend finally the proposition that a decent society must provide not only social or political but also linguistic justice by developing a substantial mulitilingualism. This multilingualism must also give the minor languages the chance to be used by a wider audience. The paper ends with two demands for the development of substantial multilingualism: the demand for an obligation to teach at least three foreign languages to every pupil at every school and the demand for an obligation to teach at least some subjects in a foreign language at every school and this foreign language should not be exclusively English.